1983
DOI: 10.1073/pnas.80.23.7070
|View full text |Cite
|
Sign up to set email alerts
|

Surface properties of an amphiphilic peptide hormone and of its analog: corticotropin-releasing factor and sauvagine.

Abstract: Synthetic corticotropin (adrenocorticotropic hormone)-releasing factor [CRF; for the sequence, see Vale, W., Spiess, J., Rivier, C. & Rivier, J. (1981) Science 213, 1394Science 213, -1397 in aqueous solution exists predominantly as a random coil. At concentrations greater than 1 ,uM, the peptide shows a tendency to self-aggregate with a concurrent slight increase in the apparent a-helical content as measured by the CD spectrum. The a-helix formed by this molecule is highly amphiphilic-i.e., the hydrophilic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
0
1

Year Published

1986
1986
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 20 publications
6
28
0
1
Order By: Relevance
“…The observed propensity of atriopeptin III to adopt a highly ordered 1-structure in such an environment is likely to be of direct relevance to the mechanism of the receptor-hormone recognition process. This is in accord with the hypothesis that the lipid phase of the target cell surface may facilitate the correct folding of the peptide hormones prior to their interaction with the receptor (23,(25)(26)(27).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The observed propensity of atriopeptin III to adopt a highly ordered 1-structure in such an environment is likely to be of direct relevance to the mechanism of the receptor-hormone recognition process. This is in accord with the hypothesis that the lipid phase of the target cell surface may facilitate the correct folding of the peptide hormones prior to their interaction with the receptor (23,(25)(26)(27).…”
Section: Resultssupporting
confidence: 77%
“…The ability of atriopeptin III to undergo conformational transitions upon binding to phospholipid membranes may be of particular significance. It has been suggested that lipid affinity plays a role in the receptor binding of many peptide hormones (22)(23)(24)(25)(26)(27). The biological action of atrial natriuretic factors is mediated by a specific hormone-receptor interaction that occurs not in aqueous medium but in the amphiphilic membrane environment (28).…”
Section: Resultsmentioning
confidence: 99%
“…By using CD (28) and NMR (29, 30) spectroscopic methods, evidence has been provided that CRF forms an amphiphilic helix whose hydrophobic patch binds to hydrophobic surfaces (31). On the basis of the helical wheel diagrams for the central parts of the peptides Svg (28) and h͞rCRF (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…20 A further SAR study, utilising an alanine replacement series of ovine CRH, found that the side chains of residues 5-19, in the N-terminal region, are important for receptor binding and activation. 22 C-Terminal amino acid residues are more responsible for structural conservation than for functional expression. The α-helix formed by CRH upon binding is highly amphiphilic in nature with hydrophobic and hydrophilic regions segregated on opposite faces of the helix.…”
Section: Crh 1 Receptor Antagonismmentioning
confidence: 99%
“…20,22 The first 8 residues are important for activation, whereas the hydrophobic side chains from amino acids 15-19 are crucial for activation of the receptor as well as its binding, the remainder of 6 the C terminus is involved in binding and is required in its entirety for full potency. 20 The C-terminal region is responsible for the formation of the α-helix.…”
mentioning
confidence: 99%